Ligand exchange processes on solvated lithium cations. VI. Determination of coordination numbers by ligand substitution and 7Li NMR - Schmeißer, Matthias; Zahl, Achim; Scheurer, Andreas; Puchta, Ralph; van Eldik, Rudi (Journal of the American Chemical Society, 2010)
On the basis of 7Li NMR studies the coordination mode of phenantroline (phen) and bipyridine (bipy) to Li+ ions was found to be [Li(phen)2]+ and [Li(bipy)2]+ in the weakly coordinating solvent nitromethane. A large chemical shift of the 7Li signal indicated a strong interaction between the ligand and the metal center. The related sp2-hybridized N-donor ligand 2, 2′-bis[(4S)-4-benzyl-2-oxazoline] (biox) showed a negligible effect on the 7Li shift, suggesting that almost no interaction occurs between the Li+ center and biox as compared to Li+ and the solvent γ-butyrolactone. Corresponding DFT (RB3LYP/LANL2DZp) calculations have clearly indicated that the poor coordination of biox is not caused by steric effects but rather by the electronic nature of the heterocyclic biox system. © 2010 Verlag der Zeitschrift für Naturforschung.
UnivIS-Import:2015-10-26:Pub.2010.nat.dchph.laoc1.ligand
Keywords: DFT calculations; Lithium complex formation; N chelates